Sosialisasi aplikasi belajar mandiri berbasis smartphone: Kamus ilmu komunikasi - Nurjayanti, Nurjayanti; Nurfida, Wa; Mayangsari, Yayu Rahmawati; Sanmas, Masni (Borneo Novelty Publishing, 2024)
The Communication Science Dictionary application was created to meet the independent learning needs of students studying the field of Communication Science. During the creation stage, the application was tested on a limited basis on students taking Communication Science courses in the Visual Communication Design study program, Makassar State University. The trial phase was continued by measuring the level of student satisfaction using the EUCS method (End User Computing Satisfaction), the results show that in terms of content, accuracy, form, ease of use, and timeliness, the application meets user satisfaction. The results of the trial and measuring the level of satisfaction became the basis for carrying out this socialization activity targeting Communication Science study program students at three other universities spread across three different provinces, namely at Muhammadiyah University of Papua, Muhammadiyah University of Buton, and Mbojo Bima University. Previously, the Communication Science Dictionary application had never been socialized and no similar application had ever been used at the three universities. The participatory method is the method applied in this service activity, where Communication Science study program students at the three universities are actively involved in using the application through smartphone each of them during the socialization activities. The result of this service is that students have independent learning media to understand various terms in the field of Communication Science.